(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This study aims to elucidate the real effectiveness of the Special Civil Courts, making a brief theoretical and historical analysis, based on great scholars, and a brief focus on the CPC, presenting the MASC its principles and its importance. Graphs of satisfaction and effectiveness of this institute will be presented, demonstrating a true instrument of social pacification, but that should be used more, as they are a mechanism for accessing justice. Thus, this study seeks to answer the reason for the slowness of Brazilian civil courts. And like mediation and conciliation, they would make less complex processes more efficient. Through bibliographical review, elaborated from the analysis and interpretation of books, periodical articles, theses and texts, published in the last decade, with reliable sources register. The methodologies used were literature review and hypothetical-deductive through which it was possible to collect relevant, relevant and extremely important data and information to know, understand and clarify problem situations, highlighting the need for proper instruction by parts of its lawyers and advocates.